Hydroelectric generator from transparent flexible zinc oxide nanofilms. (February 2017) - Li, Xuemei; Shen, Chun; Wang, Qin; Luk, Chi Man; Li, Baowen; Yin, Jun; Lau, Shu Ping; Guo, Wanlin
Abstract: Harvesting wave energy based on waving potential, a newly found electrokinetic effect, is attractive but limited mainly to monolayer graphene. Here we demonstrate that moving a transparent flexible ZnO nanofilm across the surface of ionic solutions can generate electricity. The generated electricity increases linearly with the moving velocity with an open-circuit voltage up to tens of millivolt and a short-circuit current at the order of microampere. The harvested electricity can be efficiently scaled up through series and parallel connections. Theoretical simulations show that it is the proper electrical property that endows the ZnO nanofilm with the outstanding capacity in harvesting the wave energy. Highlights: Transparent flexible ZnO nanofilms can efficiently harvest wave energy based on waving potential. It is the first time that waving potential is observed in materials other than atomically thick graphene. Deep insights into the influence of material's electrical conductivity on the induced waving potential was given.